High biocompatibility and improved osteogenic potential of novel Ca–P/titania composite scaffolds designed for regeneration of load‐bearing segmental bone defects 1. Issue 6 (22nd November 2012) - Cunha, Carla; Sprio, Simone; Panseri, Silvia; Dapporto, Massimiliano; Marcacci, Maurilio; Tampieri, Anna
Abstract: Regeneration of load‐bearing bone segments is still an open challenge due to the lack of biomaterials mimicking natural bone with a suitable chemicophysical and mechanical performance. This study proposes ceramic bone scaffolds made of β‐tricalcium phosphate (β‐TCP) and titania (TiO2 ), developed from hydroxyapatite (HA) and TiO2 starting nanopowders, which exhibit high and interconnected macroporosity (>70 vol %). The scaffold composition was designed to achieve a synergistic effect of bioactivity/resorbability and mechanical properties suitable for load‐bearing regenerative applications. The analysis of the morphology, structure, and mechanical strength of the scaffolds resulted in compression strength nearly twice that of commercially available HA bone grafts with similar structure (Engipore ® ). Biological characterization was carried out for human MG‐63 osteoblast‐like cells proliferation, activity, attachment, and viability. β‐TCP/TiO2 scaffolds show high proliferation rate, high viability, and high colonization rates. Moreover, an increased activity of the osteogenic marker alkaline phosphatase (ALP) was found. These results demonstrate that β‐TCP/TiO2 scaffolds have good potential as osteogenically active load‐bearing scaffolds; moreover, given the high and interconnected macroporosity as well as the resorbability properties of β‐TCP, these scaffolds may enhance in vivo osteointegration and promote the formation of new organized bone, thus resulting in very promising biomimetic scaffolds for long bone regeneration. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.